Effect of exercise on rehabilitation of breast cancer surgery patients: A systematic review and meta‐analysis of randomized controlled trials. Issue 4 (30th November 2022) - Lin, Yawei; Chen, Yi; Liu, Rongrong; Cao, Baohua
Abstract: Aim: To determine the effective exercise methods for different complications of breast cancer patients after surgery. Design: Systematic review and meta‐analysis. Methods: A comprehensive electronic search was carried out with no time limit until May 2020. Studies must have been randomized controlled trials of patients after breast cancer surgery, without limit to the way of exercise. Literature quality was evaluated by the modified Jadad scale. The meta‐analysis was conducted with CMA2.0 software. Results: Aerobic exercise reduced the intensity of the pain (MD = −1.043), improved shoulder flexion (MD = 3.398) and internal rotation range (MD = 3.868), lessened upper limb dysfunction (MD = −5.231) and improved muscle strength during flexion (MD = 1.076) and abduction (MD = 0.991). Shoulder elbow movement improved the range of shoulder external rotation (MD = 2.691) and reduced the incidence of arm lymphedema (RR = 0.343). Anti‐resistance exercise also lessened upper limb dysfunction (MD = − 4.094).